2010
DOI: 10.1021/om100167e
|View full text |Cite
|
Sign up to set email alerts
|

Taking Advantage of Hg−C Bonds: Synthesis of the First Homoleptic Bis-β-diketiminate Complex Bound through the γ-Carbons

Abstract: The most common β-diketiminate ligand, [{N(2,6- i Pr2C6H3)C(Me)}2CH]− (BDI), was used to synthesize a new mercury complex in which two BDI ligands are bound to the metal through the γ-carbons in the solid state. In solution, one of the BDI ligands switches to an N,N′-binding mode; this complex is in equilibrium with the homoleptic species. The thermodynamic parameters, ΔH° (−2.52 kcal mol−1), ΔS° (−9.24 cal mol−1 K−1), and ΔG°298 (0.23 kcal mol−1), were measured using variable-temperature 1H NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…An X‐ray diffraction study determined the product to be hydroxide‐bridged dimer [{(BDI)CdOH} 2 ] ( 5 ), isostructural to the Chisholm's zinc dimer [{(BDI)ZnOH} 2 ] (Figure , see Table for data‐collection parameters). [4b] Two different Cd–O bond lengths are observed for hydroxide 5 [2.2359(13) and 2.1936(12) Å], the average (2.215 Å) of which is slightly longer than that reported for the cationic hydroxo‐bridged dimer [{(ebnpa)CdOH} 2 ][ClO 4 ] 2 {average 2.206 Å; ebnpa = N ‐2‐(ethylthio)ethyl‐ N , N ‐bis[(6‐neopentylamino‐2‐pyridyl)methyl]amine} . The longer Cd–O bond corresponds to the endo cadmium–hydroxide bond and the shorter one to the exo cadmium–hydroxide bond, consistent with the exo preference for the more anionic ligand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An X‐ray diffraction study determined the product to be hydroxide‐bridged dimer [{(BDI)CdOH} 2 ] ( 5 ), isostructural to the Chisholm's zinc dimer [{(BDI)ZnOH} 2 ] (Figure , see Table for data‐collection parameters). [4b] Two different Cd–O bond lengths are observed for hydroxide 5 [2.2359(13) and 2.1936(12) Å], the average (2.215 Å) of which is slightly longer than that reported for the cationic hydroxo‐bridged dimer [{(ebnpa)CdOH} 2 ][ClO 4 ] 2 {average 2.206 Å; ebnpa = N ‐2‐(ethylthio)ethyl‐ N , N ‐bis[(6‐neopentylamino‐2‐pyridyl)methyl]amine} . The longer Cd–O bond corresponds to the endo cadmium–hydroxide bond and the shorter one to the exo cadmium–hydroxide bond, consistent with the exo preference for the more anionic ligand.…”
Section: Resultsmentioning
confidence: 99%
“…As such, other routes to β‐diketiminato group 12 complexes are required. For instance, synthesis of a three‐coordinate (β‐diketiminato)mercury complex from HgCl 2 is only successful when toluene is used as the solvent, and [Zn(N i Pr 2 ) 2 ] is a common precursor to (β‐diketiminato)zinc complexes …”
Section: Introductionmentioning
confidence: 99%
“…Although the negative charge is delocalized on the whole NCCCN ring overall, electron density in the HOMO and HOMO−1 of the BDI ligand is essentially located 10 C κ 1 -(γ-C); 11 D κ 1 -(β-C); 12 E κ 3 -(γ-C,N,N'); 13 F κ 2 -(N,N') and η 3 -(NCC); 14 G κ 2 -(γ-C,N); 15 H η 5 -Ar; 16 I κ 2 -(N,η 6 Ar). Yet, as will be described in the following discussion, tuning BDI steric and electronic properties has a strong impact on the ligand-based reactivity.…”
Section: β-Diketiminate Ligands: Nomenclature and General Propertiesmentioning
confidence: 99%
“…For example, it was shown that in the solid-state, homoleptic [Hg(BDI) 2 ] exclusively bonded through the g-carbon (8), although in solution one ligand reverts to the N,N 0 -bonding mode expected for the [BDI] À anion. 53 This is in contrast with the results from a parallel study with zinc and cadmium BDI-complexes, in which conventional N,N 0 -bonding is observed, exclusively. 54 Three independent publications involving the ferrocenyl group as a constituent within a new ligand have been presented.…”
Section: Mercurymentioning
confidence: 62%